Identification of peptide coatings that enhance diffusive transport of nanoparticles through the tumor microenvironment. Issue 38 (19th September 2019) - Mohanty, Rashmi P.; Liu, Xinquan; Kim, Jae Y.; Peng, Xiujuan; Bhandari, Sahil; Leal, Jasmim; Arasappan, Dhivya; Wylie, Dennis C.; Dong, Tony; Ghosh, Debadyuti
Abstract : High throughput phage display screening to identify peptides that enhances diffusive transport of nanoparticles through tumor microenvironment. Abstract : In solid tumors, increasing drug penetration promotes their regression and improves the therapeutic index of compounds. However, the heterogeneous extracellular matrix (ECM) acts as a steric and interaction barrier that hinders effective transport of therapeutics, including nanomedicines. Specifically, the interactions between the ECM and surface physicochemical properties of nanomedicines ( e.g. charge, hydrophobicity) affect their diffusion and penetration. To address the challenges using existing surface chemistries, we used peptide-presenting phage libraries as a high-throughput approach to screen and identify peptides as coatings with desired physicochemical properties that improve diffusive transport through the tumor microenvironment. Through iterative screening against the ECM and identification by next-generation DNA sequencing and analysis, we selected individual clones and quantify their transport by diffusion assays. Here, we identified a net-neutral charge, hydrophilic peptide P4 that facilitates significantly higher diffusive transport of phage than negative control through in vitro tumor ECM. Through alanine mutagenesis, we confirmed that the hydrophilicity, charge, and spatial ordering impact diffusive transport. The P4 phage clone exhibited almost 200-fold improved uptake in ex vivo pancreatic tumor xenografts compared to the negative control. Nanoparticles coated with P4 exhibited ∼40-fold improvement in diffusivity in pancreatic tumor tissues, and P4-coated particles demonstrated less hindered diffusivity through the ECM compared to functionalized control particles. By leveraging the power of molecular diversity using phage display, we can greatly expand the chemical space of surface chemistries that can improve the transport of nanomedicines through the complex tumor microenvironment to ultimately improve their efficacy.